Varieties of desire for peace on German postcards of World War I - Retterath, Hans-Werner (Ethnographica et Folkloristica Carpathica, 2020)
In this study the author is looking for correlations between figurative and handwritten messages on German postcards in World War I. In research literature it is mostly claimed that illustrations and news do not correlate with each other. As postcards were increasingly censored during war time and could be read by everyone the postcard writers very rarely mentioned any criticism about war matters. At first sight one can agree to this. But by deeper research of the front and back of the postcards, as well additional research in directories, archieves and historical literature the author elaborates connections between both sides and even more war criticism. On the basis of six picture postcards, mostly written by soldiers to their families the author discovers different critical attitudes towards war and peace which were depending on the actual war situation, social-cultural background of the writer himself and the offical war propaganda of those days. Sometimes the handwritten message is in contrast to the affirmative message of the postcard picture. Accordingly it can be claimed that the picture on the postcard was often used as a camouflage. Furthermore the longing for peace was mainly presented by postcard-illustrations and inscriptions with Christian references. The figurative message of these postcards were even more emphasized when the writer refered to the brutality of war.